2021
DOI: 10.1007/s11071-021-06778-5
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics of novel coronavirus SARS-CoV-2 among healthcare workers, a case study in Iran

Abstract: One of the main concerns during the COVID-19 pandemic was the protection of healthcare workers against the novel coronavirus. The critical role and vulnerability of healthcare workers during the COVID-19 pandemic leads us to derive a mathematical model to express the spread of coronavirus between the healthcare workers. In the first step, the SECIRH model is introduced, and then the mathematical equations are written. The proposed model includes eight state variables, i.e., Susceptible, Exposed, Carrier, Infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This situation is quite different from medical hospitals, in which the patients may stay for much longer periods. We used an adapted Lagrangian-type model to represent our situation, which was different from models that concern human medical hospitals, such as those in ( Evans et al, 2021 ; Gozalpour et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is quite different from medical hospitals, in which the patients may stay for much longer periods. We used an adapted Lagrangian-type model to represent our situation, which was different from models that concern human medical hospitals, such as those in ( Evans et al, 2021 ; Gozalpour et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial scales in COVID-19 models have ranged from countries and counties to cities ( Aslan et al, 2022 ; Gao et al, 2020 ; Gatto et al, 2020 ; Gumel et al, 2021 ; Macdonald et al, 2020 ; Renardy et al, 2020 ; Zhao & Feng, 2020 ). A few ODE models have represented COVID-19 transmission among health care workers in hospitals to illustrate spread and to consider interventions ( Evans et al, 2021 ; Gozalpour et al, 2021 ). No ODE models have represented the spread from interactions between the public and staff at a veterinary hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [ 17 ] studied a fractional COVID-19 model with vaccination. In [ 18 ], authors discussed the spread of COVID-19 among health workers in Iran and showed the effect of vaccination on mitigation of COVID-19 among health workers. In [ 19 ], authors proposed a robust sliding mode controller to mitigate COVID-19 spreading through social distancing, medical treatment and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, modeling and forecasting of Covid-19 in two countries, including Iran and Italy, which had different experiences during the pandemic, are conducted by using LBO algorithm and the results are compared with some other algorithms. In this regard, in spite of the myriad of the offered model [ 58 61 ], the proposed model in [ 62 ] is employed as one of the most recent popular models, and the 16-parameter model will be tuned by the proposed algorithm for available data consists of the daily number of confirmed, dead, and recovered individuals of Covid-19 between 22 January 2020 and 4 August 2021 (561 days). As a matter of fact, each 20-day time series period is divided into two parts, the first 15-day period and the last 5-day.…”
Section: Introductionmentioning
confidence: 99%